2016
DOI: 10.1039/c6en00081a
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia environmental fate and speciation of engineered nanoparticles: a probabilistic modeling approach

Abstract: The robustness of novel multimedia fate models in environmental exposure estimation of engineered nanoparticles (ENPs) is clarified by evaluating uncertainties in the emission, physicochemical properties and natural variability in environmental systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 74 publications
(194 reference statements)
4
69
1
Order By: Relevance
“…This emphasizes the need to include this process. It has been shown that because heteroaggregation captures virtually all free nanosized particles, uncertainty with respect to the exact parameterization of heteroaggregation is of minor importance [73,96,112]. The conclusions of both studies depend on the modeled scenario's and parameters' variability.…”
Section: Modeling the Transport Of Plastic Debris In The Dommel Rivermentioning
confidence: 99%
See 4 more Smart Citations
“…This emphasizes the need to include this process. It has been shown that because heteroaggregation captures virtually all free nanosized particles, uncertainty with respect to the exact parameterization of heteroaggregation is of minor importance [73,96,112]. The conclusions of both studies depend on the modeled scenario's and parameters' variability.…”
Section: Modeling the Transport Of Plastic Debris In The Dommel Rivermentioning
confidence: 99%
“…For emission-based regional estimates of environmental concentrations of plastic debris, mass balance, mass flow, and especially mechanistic multimedia models are adequate. Recently, for nanoparticles such models have been developed, like the SB4N model [63,72,73] and the MendNano model [106]. It is highly recommended that such mechanistic multimedia models are adapted for plastic as well.…”
Section: Comparing the Models: What Model For Whichmentioning
confidence: 99%
See 3 more Smart Citations